2022
DOI: 10.2138/am-2021-7818
|View full text |Cite
|
Sign up to set email alerts
|

Celleriite, ☐(Mn22+Al)Al6(Si6O18)(BO3)3(OH)3(OH), a new mineral species of the tourmaline supergroup

Abstract: Celleriite, (Mn 2+ 2 Al)Al 6 (Si 6 O 18 )(BO 3 ) 3 (OH) 3 (OH), is a new mineral of the tourmaline supergroup. It was discovered in the Rosina pegmatite, San Piero in Campo, Elba Island, Italy (holotype specimen) and in the Pikárec pegmatite, western Moravia, Czech Republic This is the peer-reviewed, final accepted version for American Mineralogist, published by the Mineralogical Society of America. The published version is subject to change. Cite as Authors (Year) Title. American Mineralogist, in press.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…Dini and Pezzotta, 2021). Among them, elbaite (Vernadsky, 1914), tsilaisite (Bosi et al ., 2012), fluor-tsilaisite (Bosi et al ., 2015b), magnesio-lucchesiite (Scribner et al ., 2021), celleriite (Bosi et al ., 2022) and uvite (this study) have Elba Island as type locality. Uvite is the second calcic tourmaline, after magnesio-lucchesiite, discovered in the San Piero in Campo area.…”
Section: Calcic Tourmalines From the Thermal Aureole Of The Monte Cap...mentioning
confidence: 80%
“…Dini and Pezzotta, 2021). Among them, elbaite (Vernadsky, 1914), tsilaisite (Bosi et al ., 2012), fluor-tsilaisite (Bosi et al ., 2015b), magnesio-lucchesiite (Scribner et al ., 2021), celleriite (Bosi et al ., 2022) and uvite (this study) have Elba Island as type locality. Uvite is the second calcic tourmaline, after magnesio-lucchesiite, discovered in the San Piero in Campo area.…”
Section: Calcic Tourmalines From the Thermal Aureole Of The Monte Cap...mentioning
confidence: 80%
“…The crystallising tourmaline registered this event with a bluish growth zone slightly richer in Fe 2+ , which ceased to grow when no more Fe was available in the system. This partial opening of the geochemical system is probably similar, but much less developed than the one associated with the formation of the well-known black-cap tourmaline crystals from Elba pegmatites (Bosi et al, 2022a). This system is likely related to more or less extensive fracturing and even pocket collapse before the end of the cavity crystallization, when abundant and reactive fluids were still present.…”
Section: Petrogenesis and Evolution Of The Blue-growth Zones In Tourm...mentioning
confidence: 85%
“…Cavities found at shallower levels contain dark-coloured tourmalines, together with pale-blue aquamarine and spessartine. On the contrary, cavities found at deeper levels contain abundant polychrome and rose tourmalines with variable Mn and Fe content, morganite, petalite, pollucite and spessartine (Orlandi and Pezzotta, 1996;Pezzotta, 2000;Bosi et al, 2022).…”
Section: Occurrence and Sample Descriptionmentioning
confidence: 99%
“…Additionally, Felch et al (2016) inferred that the observed corrosion and leaching of cavity-lining spessartine garnet crystals, was the result of reactions with late-stage hydrothermal fluids that originated and migrated from adjacent highly evolved miarolitic cavities. More recently, Bosi et al (2022) and Altieri et al (2022) proposed that the pocket rupture event, possibly related to thermal contraction during the cooling of the rock, led to some mechanical brittle deformations of the enclosing pegmatite through the formation of late-stage fractures. This allowed the highly-reactive late-stage cavity fluids to permeate the fractures surrounding the cavity where the early-crystallised cavity-lining and-coating Fe-and Mn-rich minerals were hosted.…”
Section: Introductionmentioning
confidence: 99%